Antiangiogenesis as the novel mechanism for justicidin A in the anticancer effect on human bladder cancer. Issue 4 (April 2015) - Wang, Yi-Wen; Chuang, Jing-Jing; Chang, Tsuey-Yu; Won, Shen-Jeu; Tsai, Hung-Wen; Lee, Chung-Ta; Cheng, Hong-Lin; Tzai, Tzong-Shin; Liu, Hsiao-Sheng; Chow, Nan-Haw
Abstract : Justicidin A (JA) is one of the methanol extracts of Justicia procumbens and was reported to induce apoptosis and inhibit the proliferation of human colon cancer cells. Using bladder cancer as a paradigm, this study was designed to identify the novel molecular basis underlying the antiangiogenic activities of JA and its potential in cancer therapy. Human bladder cancer cell lines (TSGH8301 and RT4) and immortalized uroepithelial cell lines (E6 and E7) were chosen to investigate the efficacy of JA in cell proliferation, apoptosis, and angiogenesis in vitro . The biological effects of JA treatment in vivo were examined using a xenograft tumor model in SCID mice. JA showed a dose-dependent and time-dependent inhibition of cell proliferation on TSGH8301 cancer cells, with IC50 values determined to be 0.44 μmol/l. Of interest, TSGH8301 cancer cells were more sensitive to JA than E7 immortalized uroepithelial cells, especially at lower concentrations. We further showed that JA inhibited the autocrine production of angiogenic factors and matrix-degrading enzymes in vitro and microvessel density in SCID mice in vivo ( P < 0.01). Both differential cytotoxicity and angiogenesis inhibition of JA were confirmed by SCID mice experiments. Together, JA showed antiangiogenesis in vitro and in vivo through pleiotropic positive and negative regulators of angiogenesis molecules. The current investigation supports the potential of JA as an alternative chemoprevention agent for human bladder cancer. Abstract : Supplemental Digital Content is available in the text.